FRaeppli: A multispectral imaging toolbox for cell tracing and dense tissue analysis in zebrafish - Caviglia, Sara; Unterweger, Iris A.; Gasiunaite, Akvile; Vanoosthuyse, Alexandre E.; Cutrale, Francesco; Trinh, Le A.; Fraser, Scott E.; Neuhauss, Stephan C.F.; Ober, Elke Annette (Development, 2022)
Visualizing cell shapes and interactions of differentiating cells is instrumental for understanding organ development and repair. Across species, strategies for stochastic multicolour labelling have greatly facilitated in vivo cell tracking and mapping neuronal connectivity. Yet integrating multi-fluorophore information into the context of developing zebrafish tissues is challenging given their cytoplasmic localization and spectral incompatibility with common fluorescentmarkers. Inspired by Drosophila Raeppli, we developed FRaeppli (Fish-Raeppli) by expressing bright membrane- or nuclear-targeted fluorescent proteins for efficient cell shape analysis and tracking. High spatiotemporal activation flexibility is provided by the Gal4/UAS system together with Cre/lox and/or PhiC31 integrase. The distinct spectra of the FRaeppli fluorescent proteins allow simultaneous imaging with GFP and infrared subcellular reporters or tissue landmarks. We demonstrate the suitability of FRaeppli for live imaging of complex internal organs, such as the liver, and have tailored hyperspectral protocols for time-efficient acquisition. Combining FRaeppli with polarity markers revealed previously unknown canalicular topologies between differentiating hepatocytes, reminiscent of the mammalian liver, suggesting common developmental mechanisms. The multispectral FRaeppli toolbox thus enables the comprehensive analysis of intricate cellular morphologies, topologies and lineages at single-cell resolution in zebrafish.
Created from Fastlane, Scopus look-up
Keywords: Canaliculi topology; Cell shape; Liver; Multicolour cell labelling; PhiC31 integrase; Zebrafish